THE INFLUENCE OF SOTE OF DESIGN DECISIONS IN RAISING THE COST oF D*ELLING uNlr - Youssef, Nagham Faisal; Abdel Amir, Nawal Abdel Amir; Nihad, Meaning Nihad (Iraqi Journal of Architecture and Planning, 2018)